Improving The Adiwiyata Program on Emancipated Learning to Strengthen Local Wisdom Values in Madrasah Ibtidaiyah - Sholihah, Mar'atus (Proceedings of Annual Conference for Muslim Scholars, 2024)
Jember society is reported to have a lack of awareness of maintaining the environment and sustaining local wisdom in school. It is essential to implement the Adiwiyata Program for madrassa ibtidaiyah students since at this age pupils tend to absorb knowledge as well as habits strongly and this type of school also teaches Islamic virtues. This article aims to narrate the Adiwiyata Program on emancipated learning at Madrassa Ibtidaiyah 45 Paseban-Kencong and State Madrassa Ibtidaiyah 2 Balung-Jember. This research used a qualitative method with a case study to describe the Adiwiyata Program supported by observation, interview, and documentation data. The results of this study explained that students can strengthen local wisdom through four indicators: 1) environmentally sustainable policy; 2) environmentally-based curriculum implementation; 3) participatory environment-based activities; and 4) environmentally friendly support facilities management. These schools applied those indicators on emancipated learning for madrassa ibtidaiyah students in grades 1st to 6th.